The Old Testament in Translated Patristic Works: Ezekiel 1–4:3 and 40:1–47 in Fr. Gonzalo de Ocaña's (1442) Spanish Translation of Homiliarum in Ezechielem Prophetam libri duo by Pope Gregory I. - Avenoza, Gemma (Medieval Encounters, 2020)
This study explores the political and cultural context of Fr. Gonzalo de Ocaña's translation of the Homiliarum in Ezechielem of Pope Gregory I. It sheds light on the personality of the translator, offering new information about his life. It also delves into the political circumstances in which Queen María of Castile requested this translation from her chaplain. In fact, Ocaña's prologue to his translation provides unique historical evidence of his own personal position vis-à-vis the political strife between the Queen's brothers and her husband, John II of Castile, a struggle that had brought Castile close to ruin. The translation of this patristic text is also important because it provides us with a literal version of extensive passages from the Book of Ezequiel and constitutes the only known translation of this book of the Old Testament made from the Vulgata in the fifteenth century. Ocaña's use of the Latin source is by no means a trivial issue, for the only two known versions of the Book of Ezekiel translated from Latin into Spanish, the pre-Alfonsine Bible and the General estoria , were prepared much earlier, in the thirteenth century.